The Effect of Education and Gender on Language Proficiency: A Study of Multilingual Hungarian Young Adults’ Verbal Fluency - Noémi Szabó; Failasofah Failasofah (Universitas Jambi, Indonesia, 2021)
Recent developments in the field of multilingual processing have led to a renewed interest in exploring the effect of verbal fluency tasks from a new perspective (Shishkin & Ecke, 2018). This Hungarian case study intends to investigate the effect of verbal fluency tasks on multilingual participants’ language proficiency with special attention to gender differences and educational background. Six participants were recruited to take part in the study: three males and three females. Respondents’ first language (L1) was Hungarian while their two foreign languages include English (L2/ L3) and German (L2/ L3). Data for this study were collected by using verbal fluency tasks, namely phonological and semantic fluency tests. Data management and analysis were performed using SPSS 22. The results suggest that students outperformed their graduate peers. The majority of the participants obtained better scores in English in terms of semantic fluency meanwhile most of the subjects achieved greater results in German as for the phonemic category. Female participants outperformed males both in the majority of phonemic and semantic tasks.